A yellow-emitting nitrogen-doped carbon dots for sensing of vitamin B12 and their cell-imaging. (May 2020) - Sun, Zishan; Chen, Zikang; Luo, Jiabao; Zhu, Zhenpeng; Zhang, Xinguo; Liu, Ruiyuan; Wu, Zhan-chao
Abstract: A simple approach for the synthesis of novel yellow luminescent carbon dots (Y-CDs) has been developed via solvothermal method using l -tartaric acid and urea as precursors. The obtained Y-CDs were found to emit bright yellow luminescence under UV illumination with a quantum yield of 16.7%. Meanwhile, the Y-CDs exhibited excitation-dependence, photo-stability, and well dispersibility. The Y-CDs efficiently and selectively detected the VB12 in aqueous solution through a fluorescent "Turn Off" phenomenon. Excellent linear relationship between Y-CDs emission ratio and VB12 concentration from 0 μM to 200 μM is observed, in which the correlation coefficient is 0.997 and the detection limit is 2.045 μmol/L. The quenching mechanism was investigated through proper microscopic and spectroscopic studies. In a parallel experiment, the Y-CDs were used as a cell-imaging probe for MDA-MB-231 cells. Our results demonstrated that as-obtained Y-CDs can be simply used as versatile probes, highlighting their potential in different biological studies. Graphical abstract: A novel N-doped yellow-emitting carbon dots (Y-CDs) for VB12 sensing and cellular imaging were synthesized via solvothermal method. The Y-CDs displays a yellow emission at 550 nm (QY = 16.7%) and exhibits a high-selective and well-linear relationship between integrated intensity and VB12 concentration in 0–200 μmol/L range. Furthermore, Y-CDs possess good bio-compatibility and can be used for cell imaging as excellent fluorescence probes. Image 1 Highlights: A novel efficient yellow-emitting CDs (Y-CDs) was synthesized by simple solvothermal method. The Y-CDs showed selective and sensitive VB12 detection with inner filter effect as sensing mechanism. The biocompatibility and photostability of carbon dots were excellent. The as-synthesized carbon dots exhibited high efficiency for cell imaging.